Foliar application of nano biochar solution elevates tomato productivity by counteracting the effect of salt stress insights into morphological physiological and biochemical indices - Javeria Shahzadi; Zaib-un-Nisa; Naila Ali; Muhammad Iftikhar; Anis Ali Shah; M. Yasin Ashraf; Chen Chao; Shifa Shaffique; Mansour K. Gatasheh (Scientific Reports)
Abstract Nano-biochar considers a versatile and valuable sorbent to enhance plant productivity by improving soil environment and emerged as a novel solution for environmental remediation and sustainable agriculture in modern era. In this study, roles of foliar applied nanobiochar colloidal solution (NBS) on salt stressed tomato plants were investigated. For this purpose, NBS was applied (0%, 1% 3% and 5%) on two groups of plants (control 0 mM and salt stress 60 mM). Tween-20 was used as a surfactant to prolong NBS effective stay on plant leaf surface. The results showed that 3% NBS application effectively improved the plant height, plant biomass, fruit count and fruit weight under non-stressed and stressed plants. In addition, 3% NBS application further increased the plant pigments such as chlorophyll by 72% and 53%, carotenoids by 64% and 40%, leaf relative water content by 4.1 fold and 1.07 fold under both conditions, respectively. NBS application stabilized the plasma membrane via reducing electrolyte leakage by 30% as well as reduced the lipid peroxidation rates by 46% and 29% under non-stressed and stressed plants, respectively. 3% NBS application also significantly enhanced the plants primary and secondary metabolites, as well as activities of antioxidant enzymes compared to control plants. Overall, NBS foliar application significantly improved all growth and yield indices, pigments, primary and secondary metabolites, leaf water content, antioxidant enzyme activities as well as reduced electrolyte leakage and lipid peroxidation rates in tomato to combat stress conditions. In future, studies on nano biochar interactions with soil microbiota, surface modifications, long-term environmental impacts, reduced methane gas emissions, and biocompatibility could provide insights into optimizing its use in sustainable agriculture.